2013
DOI: 10.1097/phm.0b013e31827d6546
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Multiple F-wave Variable Studies and Magnetic Resonance Imaging Examinations in the Assessment of Cervical Radiculopathy

Abstract: There was a low correlation between F-wave studies and magnetic resonance imaging examinations. The diagnostic utility of multiple F-wave variables in the prediction of cervical radiculopathy was not supported by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, a retrospective study reviewing patients operated on for cervical radiculopathy during a 10-year period concluded neurophysiological testing had limited additional diagnostic value [42]. A recent study on the diagnostic utility of multiple F-wave variables in the prediction of cervical radiculopathy concluded there was a low correlation between F-wave studies and MRI examinations and could therefore not support its use as such [44].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, a retrospective study reviewing patients operated on for cervical radiculopathy during a 10-year period concluded neurophysiological testing had limited additional diagnostic value [42]. A recent study on the diagnostic utility of multiple F-wave variables in the prediction of cervical radiculopathy concluded there was a low correlation between F-wave studies and MRI examinations and could therefore not support its use as such [44].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…By means of the F-wave test, it is possible to isolate the damage of only one root due to the innervation of several root levels of muscles from which this response is recorded [2, 22]. Lin et al [23] carried out a detailed analysis of patients with cervical radiculopathy confirmed by an MRI at the C7 and C8 roots. They obtained F-wave recordings after a simulation of the median and ulnar nerves.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with Lin's study. Lin et al showed that F wave latencies in patients with cervical radiculopathies were not significant when they were adjusted for height and age (6).…”
Section: Discussionmentioning
confidence: 99%
“…EDX, a neuro-physiological investigation, detects functional abnormalities of nerve root as well as intensity and duration of the disease (4). F wave study, part of EDX, has had a controversial sensitivity in diagnosing radiculopathies in different studies (5)(6)(7)(8)(9)(10). For instance, a study showed that comparing F-wave parameters in two limbs can be beneficial in detecting unilateral S 1 radiculopathy and reduce the false negative results of this assessment (11)(12).…”
Section: Mri and Electrodiagnostic Study (Edx)mentioning
confidence: 99%